2015
DOI: 10.1371/journal.pntd.0004152
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Responses Are Associated with Survival in Acute Melioidosis Patients

Abstract: BackgroundMelioidosis is an increasingly recognised cause of sepsis and death across South East Asia and Northern Australia, caused by the bacterium Burkholderia pseudomallei. Risk factors include diabetes, alcoholism and renal disease, and a vaccine targeting at-risk populations is urgently required. A better understanding of the protective immune response in naturally infected patients is essential for vaccine design.MethodsWe conducted a longitudinal clinical and immunological study of 200 patients with mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(130 citation statements)
references
References 48 publications
13
108
2
Order By: Relevance
“…pseudomallei and the development of adaptive immunity, suppressed T-cell responses to B . pseudomallei are associated with death from acute melioidosis [19]. However, we did not find evidence that the TLR5 c.1174C>T variant drives the T-cell IFN-γ response, IHA titer, or anti-FliC antibody response during acute melioidosis, suggesting that the mechanism of enhanced survival in carriers of the TLR5 variant may be independent of these adaptive immunological responses.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…pseudomallei and the development of adaptive immunity, suppressed T-cell responses to B . pseudomallei are associated with death from acute melioidosis [19]. However, we did not find evidence that the TLR5 c.1174C>T variant drives the T-cell IFN-γ response, IHA titer, or anti-FliC antibody response during acute melioidosis, suggesting that the mechanism of enhanced survival in carriers of the TLR5 variant may be independent of these adaptive immunological responses.…”
Section: Discussioncontrasting
confidence: 65%
“…pseudomallei at a young age, indicating that environmental exposure to the bacterium and the development of adaptive immune responses in the absence of clinical infection is common [18]. A previous study in this cohort reported reduced T-cell responses in patients with acute melioidosis that did not survive [19], raising the possibility that c.1174C>T may protect against death by enhancing T-cell mediated immunity against B . pseudomallei .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vaccine designs directed at providing complete protection also need to induce cell-mediated immunity (For example, [58,87]). Consistent with this, human patient survivors of culture-confirmed acute melioidosis displayed an increased frequency of CD4 + and CD8 + T cells, while a decrease in CD4 + and CD8 + IFN-γ-producing T cells was specifically correlated with increased mortality, further highlighting a pivotal contribution by cellular immunity to control melioidosis [106]. Furthermore, vaccines eliciting Th1-like biased immune responses or incorporating Th1-promoting adjuvants have been demonstrated to be protective against melioidosis and glanders in mice and may have the potential to induce sterile immunity (As reviewed in [61] [56] [4]).…”
Section: Expert Commentarysupporting
confidence: 66%
“…This correlates with our previous studies showing that human antibodies and PBMCs can recognize FliC and OmpA proteins, and the magnitude of the response from human seropositive individuals is higher than for seronegative individuals. 9,52 Hence, the difference of IFN-c production in response to B. pseudomallei between seropositive and seronegative individuals seen Antibody avidities of IgM and IgG were evaluated by using indirect ELISA following treatment with 7 M urea (n = 5). 9,51,52 During IFN-c production upon stimulation of human seropositive PBMCs with B. pseudomallei, NK cells are transient and are prominent in the first 24 hr of stimulation whereas CD4 and CD8 T cells have more contribution in the later phase of stimulation by a primary response through terminally differentiated effector memory T cells.…”
Section: Discussionmentioning
confidence: 99%